Spatial patterns of cultural ecosystem services provision in Southern Patagonia - Martinez Pastur, Guillermo José (2016)
Context Although there is a need to develop a spatially explicit methodological approach that addresses the social importance of cultural ecosystem services for regional planning, few studies have analysed the spatial distribution on the cultural ecosystem services based on social perceptions. Objective The main objective of this study was to identify cultural ecosystem service hot-spots, and factors that characterize such hot-spots and define the spatial associations between cultural ecosystem services in Southern Patagonia (Argentina). Methods The study was carried out in Southern Patagonia (243.9 thousand km2) located between 46° and 55° SL with the Andes mountains on the western fringe and the Atlantic Ocean on the eastern fringe of the study area. The study region has a range of different vegetation types (grasslands, shrub-lands, peat-lands and forests) though the cold arid steppe is the main vegetation type. We used geo-tagged digital images that local people and visitors posted in the Panoramio web platform to identify hot-spots of four cultural ecosystem services (aesthetic value, existence value, recreation and local identity) and relate these hot-spots with social and biophysical landscape features. Results Aesthetic value was the main cultural service tagged by people, followed by the existence value for biodiversity conservation, followed by local identity and then recreational activity. The spatial distribution of these cultural ecosystem services are associated with different social and biophysical characteristics, such as the presence of water bodies, vegetation types, marine and terrestrial fauna, protected areas, urbanization, accessibility and tourism offer. The most important factors are the presence of water in Santa Cruz and tourism offer in Tierra del Fuego.